Corybas circinatus (Orchidaceae), a new species from Palawan, the Philippines - Tandang, Danilo N.; Bustamante, Rene Alfred Anton; Ferreras, Ulysses; Hadsall, Annalee S.; Pym-Lyon, Stephanie; Robinson, Alastair S. (Phytotaxa, 2020)
Corybas circinatus, a new species of helmet orchid endemic to ultramafic habitats on the island of Palawan, Philippines, is hereby described and illustrated. This species is distinct in bearing a small glandular protuberance at the front of its pedicel, a 4-lobed entire labellum, and a distinctive strongly incurved dorsal sepal. The general colouration of the floral and vegetative parts is also highly characteristic, and the general lowland to mid-montane ecology of the species is unique amongst the known Philippines Corybas.